Hepatitis E Virus (HEV) infection in captive white‐collared peccaries (Pecari tajacu) from Uruguay. Issue 3 (29th August 2020) - Ferreiro, Irene; Herrera, María Laura; González, Ignacio; Cancela, Florencia; Leizagoyen, Carmen; Loureiro, Matías; Arellano, Hugo; Echaides, César; Bon, Brenda; Castro, Gustavo; Arbiza, Juan; Mirazo, Santiago
Abstract: Hepatitis E virus (HEV) infection is a major cause of acute hepatitis worldwide. Clinical presentation of hepatitis E mainly occurs as an acute and self‐limited disease, though chronic cases are now being commonly reported in immunocompromised individuals. In high‐income developed areas and non‐endemic regions, HEV is mainly transmitted by the zoonotic route through direct contact with infected animals or by consumption of contaminated meat products. Although pigs and wild boars are the main reservoirs of the disease, HEV can also infect deer, camels, and rats and seems to have an ever‐expanding host range. Peccaries ( Tayassuidae family, superfamily Suoidea), the 'new world pigs', share susceptibility to several pathogens with domestic pigs and wild boars. Herein, we performed a serological and molecular survey of two captive populations of white‐collared peccaries ( Pecari tajacu ) from Uruguay, with the aim to assess the role of the species as an HEV reservoir. One‐hundred and one serum samples were analysed for anti‐HEV antibodies. Further evidences of active HEV infection were investigated in stool by RT‐nested PCR. Animals from both wildlife reserves were exposed to HEV with an overall prevalence of 24.7%. Moreover, HEV RNA could be detected in peccaries' stool samples from one of the reserves. Phylogenetic analysis clustered the strains within HEV‐3, closely related to both human and swine isolates. Our work provides the first evidences supporting the notion that white‐collared peccaries are susceptible to HEV. However, these data should not be overinterpreted. Further research is needed concerning the role of peccaries in the transmission of HEV.